Media Pembejaran tentang Hewan Menggunakan Adobe Flash Cs6 - Mira Handayani Siregar; Syaiful Zuhri Harahap; Musthafa Haris Munandar; Masrizal; Marnis Nasution; Irmayanti; Rahma Muti Ah; Megawati Pasaribu (Majalah Ilmiah UPI YPTK, 2020)
The Development Of Science And Technology Is So Rapid And Has A Big Influence On The Teaching And Learning Process. The Learning Media Used By The Teacher Has A Major Influence In Increasing Interest And Accelerating Students' Understanding Of The Material Presented By The Teacher. As A Result Of These Technological Advances, Various Applications Began To Appear That Were Made To Assist The Process Of Teaching And Learning Activities, However, There Are Still Many Early Childhood Schools That Have Not Utilized Animation-Based Applications. Animal Recognition Learning Media Uses Adobe Flash Cs6 For Student Learning Facilities, Especially Paud Al-Azis To Help Teachers In Teaching And Learning Activities To Be More Interactive And Fun. This Introduction To Animals Is Made To Increase The Knowledge Of Early Childhood Students In Recognizing Animals And Questions Related To Animals And Starting With Learning Using Animation-Based Applications